Dynamics of Andaman Sea circulation and its role in connecting the equatorial Indian Ocean to the Bay of Bengal. Issue 4 (13th April 2017) - Chatterjee, Abhisek; Shankar, D.; McCreary, J. P.; Vinayachandran, P. N.; Mukherjee, A.
Abstract: Circulation in the Bay of Bengal (BoB) is driven not only by local winds, but are also strongly forced by the reflection of equatorial Kelvin waves (EKWs) from the eastern boundary of the Indian Ocean. The equatorial influence attains its peak during the monsoon‐transition period when strong eastward currents force the strong EKWs along the equator. The Andaman Sea, lying between the Andaman and Nicobar island chains to its west and Indonesia, Thailand, and Myanmar to the south, east, and north, is connected to the equatorial ocean and the BoB by three primary passages, the southern (6°N), middle (10°N), and northern (15°N) channels. We use ocean circulation models, together with satellite altimeter data, to study the pathways by which equatorial signals pass through the Andaman Sea to the BoB and associated dynamical interactions in the process. The mean coastal circulation within the Andaman Sea and around the islands is primarily driven by equatorial forcing, with the local winds forcing a weak sea‐level signal. On the other hand, the current forced by local winds is comparable to that forced remotely from the equator. Our results suggest that the Andaman and Nicobar Islands not only influence the circulation within the Andaman Sea, but also significantly alter the circulation in the interior bay and along the east coast of India, implying that they need to be represented accurately in numerical models of the Indian Ocean. Key Points: First modeling study of the dynamics of the Andaman Sea Sea level in Andaman Sea forced by equatorial winds, but local winds force comparable currents Interference between Rossby waves and the islands influences circulation in the Bay of Bengal